2017
DOI: 10.1111/ajpy.12119
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary nurses' psychological well‐being: The impact of patient suffering and death

Abstract: Objective: Preliminary evidence suggests veterinary nurses are an at-risk population for high levels of occupational stress. This study sought to advance knowledge of occupational stress in this under-researched professional group by applying the Job Demands-Resources model to assess predictors of psychological strain, work-related burnout, and work engagement. Method: Research participants consisted of 144 veterinary nurses employed within one Australian state (response rate of 41%). Data were obtained via an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…Frequency of euthanasia demonstrated no significant relationship to psychological distress or compassion fatigue, contrary to other findings in veterinarians and veterinary nurses . Performing euthanasia has been linked to higher work stress and lower job satisfaction not only in veterinarians but also animal care workers from other animal related industries whose role involves performing euthanasia .…”
Section: Discussioncontrasting
confidence: 73%
“…Frequency of euthanasia demonstrated no significant relationship to psychological distress or compassion fatigue, contrary to other findings in veterinarians and veterinary nurses . Performing euthanasia has been linked to higher work stress and lower job satisfaction not only in veterinarians but also animal care workers from other animal related industries whose role involves performing euthanasia .…”
Section: Discussioncontrasting
confidence: 73%
“…Perhaps it is not surprising, given the technicians' job duties, that preliminary studies indicate that veterinary technicians are also at high risk for occupational stress and burnout (30,40). One study found factors predictive of increased burnout for technicians include work load, job demands, exposure to euthanasia and contact with clients (34).…”
Section: Introductionmentioning
confidence: 99%
“…The current study was designed to identify factors that may improve veterinary technicians' work experience by mitigating burnout. As noted above, very little research has examined the extent to which veterinary technicians' work is intellectually fulfilling and rewarding or how they apply and acquire a variety of skills that they can use in complex problem solving (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there has been little research carried out regarding occupational stress in the veterinary nursing profession, available evidence suggests that there are veterinary nurses working in the profession who regard their role as stressful [ 3 , 4 ]. Whilst occupational stress is not a unique concept relating to members of the human or animal health care sectors, there are unique occupational stressors, such as euthanasia, which members of the animal health care sector are exposed to in comparison to other health care professions, and non-health care workers [ 3 , 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%